Students’ Memory Ability: The Use of Prompt-Based Artificial Intelligence in Learning - Cahyo, Dwi Irfan; Widyanti, Dini Nur; Novitasari, Nadyta Aulia Dwi (The Future of Education Journal, 2026)
This study examines students’ memory ability through the use of prompt-based artificial intelligence (AI) in learning. The background of this research is the increasing utilization of AI by students to complete academic tasks, which may reduce their attention to teachers’ explanations and lead to superficial learning processes. The main problem identified is the declining interest of students in independently training their memory skills, resulting in suboptimal long-term cognitive development. Therefore, this study aims to identify implementation strategies of AI in learning and to analyze the effect of prompt-based AI usage on students’ memory ability. This research employed a quantitative approach with a quasi-experimental method using a Nonequivalent Control Group Design. The sample consisted of 72 students selected from a population of 319 students at SMA Negeri 1 Kedungadem through probability random sampling. Data were collected through observation, pre-test and post-test instruments, documentation, and Likert-scale questionnaires. Data analysis was conducted using a paired sample t-test with the assistance of SPSS version 26. The findings reveal that prompt-based AI media significantly improved students’ memory ability in sociology learning for classes XI-7 and XI-8. The mean pre-test score increased from 59.56 to 69.42 in the post-test, with a significance value of 0.000 < 0.05, indicating that the research hypothesis was accepted. The novelty of this study lies in highlighting the role of prompt-based AI not only as a learning support tool but also as a medium to enhance concentration, strengthen memory retention, and promote students’ learning independence. Thus, AI can be utilized as a balanced learning medium that integrates technology, cognitive function, and social interaction.